BK Polyomavirus-specific T Cells as a Diagnostic and Prognostic Marker for BK Polyomavirus Infections After Pediatric Kidney Transplantation. Issue 11 (November 2020) - Ahlenstiel-Grunow, Thurid; Sester, Martina; Sester, Urban; Hirsch, Hans H.; Pape, Lars
Abstract : Background: After kidney transplantation, uncontrolled BK polyomavirus (BKPyV) replication causes kidney graft failure through BKPyV-associated nephropathy (BKPyVAN), but markers predicting outcome are missing. BKPyV-specific T cells may serve as a predictive marker to identify patients at risk of persistent DNAemia and BKPyVAN. Methods: Out of a total of 114 pediatric kidney recipients transplanted between 2008 and 2018, 36 children with posttransplant BKPyV-DNAemia were identified. In a prospective noninterventional study, BKPyV-specific CD4 and CD8 T cells were measured in 32 of 36 viremic pediatric kidney recipients using intracellular cytokine staining and flow cytometry. The course of the BKPyV replication was monitored with regard to duration of BKPyV-DNAemia and need of therapeutic intervention and diagnosis of proven BKPyVAN. Results: Levels of BKPyV-specific T cells negatively correlated with subsequent duration of BKPyV-DNAemia. Patients with BKPyV-specific CD4 T cells ≥0.5 cells/µL and/or BKPyV-specific CD8 T cells ≥0.1 cells/µL had transient, self-limiting DNAemia (PPV 1.0, NPV 0.86). BKPyV-specific CD4 and CD8 T cells below these thresholds were found in children with persistent BKPyV-DNAemia and biopsy-proven BKPyVAN with need for therapeutic intervention. After reducing immunosuppressive therapy, levels of BKPyV-specific CD4 T cells increased while plasma BKPyV-DNAemia declined. Conclusions: This study found that BKPyV-specific T cell levels may help to distinguish patients with transient, self-limiting BKPyV-DNAemia from those with persisting BKPyV-DNAemia and biopsy-proven BKPyVAN, who would benefit from individualized therapeutic interventions such as reduced immunosuppression. Thereby the risk for rejection because of unnecessary reduction of immunosuppression in case of self-limiting BKPyV-DNAemia can be minimized. Abstract : Supplemental Digital Content is available in the text.